Green Accounting In Village-Owned Business Entities Using Environmental Accounting - Abdul Manap1; Mohammad Djauhari; Muhammad Yasin; Ikhwan Ikhwan; Adnedi Adnedi (Jurnal Mirai Management, 2023)
The process of finding, recognising, measuring, presenting, and disclosing all corporate expenditures made to enhance environmental quality by preventing, mitigating, and even avoiding negative environmental impacts is known as "green accounting." Researchers at BUMDES Banyuresmi conducted an investigation of environmental accounting (green accounting) with the aim of figuring out how environmental accounting was applied by BUMDES to waste management. This inquiry makes use of a descriptive approach. Interviews and documentation were both employed as data collection methods. The analysis of the data was qualitatively descriptive. The results show that BUMDES Banyuresmi has implemented environmental accounting, which entails five processes for allocating costs associated with waste management: identification, recognition, measurement, presentation, and disclosure. Thoughts for future concerns are needed because the presentation and disclosure phases do not follow generally accepted accounting principles. Key Word : green accounting, Accounting environment, BUMDES.